Oral acetylsalicylic acid and prevalence of actinic keratosis - Schmit, Juliano [UNESP]; Miot, Hélio Amante [UNESP] (Associação Médica Brasileira, 2014)
Objective: To investigate the influence of a regular oral use of acetylsalicylic acid in the prevalence of actinic keratosis.Methods: A case-control study with dermatologic outpatients above 50 years of age assessed between 2009 and 2011. Cases were defined as those who had been under regular use of oral acetylsalicylic acid for more than six consecutive months. The assessment focused on: age, sex, skin-type, tobacco smoking, use of medication, occurrence of individual or family skin cancer, and sunscreen and sun exposure habits. Actinic keratoses were counted in the medial region of the face and upper limbs. Counts were adjusted by co-variables based on a generalized linear model.Results: A total of 74 cases and 216 controls were assessed. The median time of acetylsalicylic acid use was 36 months. Cases differed from controls as to the highest age, highest prevalence of use of angiotensin-converting enzyme inhibitors and fewer keratosis on the face and on the upper limbs (p < 0.05). The multivariate model showed that the use of acetylsalicylic acid was associated to lower counts of face actinic keratosis and upper-limb erythematous actinic keratosis (p < 0.05), regardless of other risk factors.Conclusion: The regular use of oral acetylsalicylic acid for more than six months was associated to a lower prevalence of actinic keratosis, especially facial and erythematous ones.
Keywords: actinic keratosis; acetylsalicylic acid; prevalence; risk factors